SACRIFICE AS DESCRIBED IN OSCAR WILD’S THE NIGHTINGALE AND THE ROSE - JESSICA K TUNGKA,; Olga Rorintulus; Fivy A. Andries (Program Studi Pendidikan Bahasa Inggris, 2022)
This study was conducted to describe sacrifice and explain its actions and values of sacrifice in Oscar Wild’s The Nightingale and the Rose. This study was focused only to analyze sacrifice in Oscar Wild’s The Nightingale and the Rose. More specifically, the focus will be on the sacrifice done by The Nightingale. This research used qualitative research design because the data are in the form of quotation or description. In carrying out this research, the data were collected from the short story written by Oscar Wild entitled The Nightingale and the Rose as primary source and also supported by other relevant references such as books, documents and web sources about sacrifice which considered as secondary source. In analyzing the data collected, the researcher applied objective approach and describe the sacrifice and its actions and values in the short story. The findings demonstrate that giving attention, showing affection, and self-sacrifice are actions of sacrifice, whereas unconditional love and risk-taking are values of sacrifice.